2004
DOI: 10.1049/ip-nbt:20040535
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale surface engineered living cells with extended substrate spectrum

Abstract: We report on cell surface engineering of living microorganisms by using Layer-by-Layer (LbL) technology to extend the substrate spectrum. The yeast Arxula adeninivorans LS3 (Arxula) was employed as a model organism and biological template. By using LbL technology, Arxula cells were encapsulated by polyelectrolyte and enzyme layers. The biological activity of the Arxula was retained after the encapsulation process. The polymeric capsule surrounding the Arxula provides a stable interface for surface engineering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…[85] The absence of such cofactors in dead cells leads to no conversion and no fluorescence can be detected. [86] Figure 7 shows viability of cells encapsulated with truly nonionic LbL shells in comparison with the same cells encapsulated but with cationic PEI pre-layer as a control series explored in previous study with different PVPON molecular weight. [61] In this study, different molecular weights of PVPON (360 or 1 300 kDa) and different numbers of TA/PVPON bilayers (two or four) have been explored.…”
Section: Viability and Growth Of Encapsulated Cells With Different Shmentioning
confidence: 99%
“…[85] The absence of such cofactors in dead cells leads to no conversion and no fluorescence can be detected. [86] Figure 7 shows viability of cells encapsulated with truly nonionic LbL shells in comparison with the same cells encapsulated but with cationic PEI pre-layer as a control series explored in previous study with different PVPON molecular weight. [61] In this study, different molecular weights of PVPON (360 or 1 300 kDa) and different numbers of TA/PVPON bilayers (two or four) have been explored.…”
Section: Viability and Growth Of Encapsulated Cells With Different Shmentioning
confidence: 99%
“…[16,17] Furthermore, different yeast species have been encapsulated, and for Arxula adeninivorans LS3, LbL nano self-assembly demonstrated a spectrum of substrate utilization. [18,19] These studies show the promising prospects for the application of LbL nano self-assembly on questions in microbiology because the method allows construction of cell surfaces with a defined architecture on living and metabolically active microorganisms, while the complete shell characterizes cell colloidal stability, and the outermost layer characterizes the surface charge and a specific hydrophilicity or hydrophobicity. [20] Furthermore, defining the incorporation (uptake) and defined release of different molecules, like proteins or nanoparticles in the shells, are possible for eukaryotes and prokaryotes.…”
Section: Introductionmentioning
confidence: 98%
“…[17] Therefore, it was the aim of our investigations to demonstrate substrate uptake for bacteria, similar to experiments done with the eukaryotic A. adeninivorans LS3. [19] As a model organism with a versatile sulfur metabolism, the gram-negative, phototrophic purple sulfur bacterium Allochromatium vinosum was chosen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such result shed light on the feasibility of manipulating the function of single cells by LbL cell encapsulation. From then on, several researches focused on the encapsulation of yeast and bacterial spore by LbL assembly and observe the viability and metabolic activity changes of the encapsulated cells . For example, Diaspro et al reported the encapsulation of yeast ( S. cerevisiae ) with PAH and PSS and observed that microbial cells maintained their normal metabolic activities and viability after encapsulation .…”
Section: Strategies Of Lbl Self‐assembly Technique For Cell Encapsulamentioning
confidence: 99%